Tax rate cuts and tax compliance – the Laffer curve revisited - Papp, Tamás K.; Takáts, Előd (Public Finance Quarterly, 2024)
he paper shows how tax rate cuts can increase revenues by improving tax compliance. The intuition is that tax evasion has externalities: tax evaders protect each other, because they tie down limited enforcement capacity. Thus, relatively small tax rate cuts, which decrease incentives to evade taxes, can lead to increased revenues through spillovers – creating Laﬀer eﬀects. Interestingly, cutting de facto tax rates imply increasing de facto or eﬀective tax rates. The model is consistent with the consequences of Russian tax reform, and may provide basis for further thinking about tax rate cuts in other countries.